The oscillation of mitotic kinase governs cell cycle latches in mammalian cells - Dragoi, C-M; Kaur, E; Barr, AR; Tyson, JJ; Novak, B (Company of Biologists, 2024)
The mammalian cell cycle alternates between two phases: S-G2-M with high levels of A- and B-type cyclin-dependent kinases (CycA,B:CDK); and G1 with persistent degradation of CycA,B by Cdh1-activated APC/C (anaphase promoting complex/cyclosome). Because CDKs phosphorylate and inactivate Cdh1, these two phases are mutually exclusive. This 'toggle switch' is flipped from G1 to S by cyclin-E (CycE:CDK), which is not degraded by Cdh1:APC/C; and from M to G1 by Cdc20:APC/C, which is not inactivated by CycA,B:CDK. After flipping the switch, cyclin E is degraded and Cdc20:APC/C is inactivated. Combining mathematical modelling with single-cell timelapse imaging, we show that dysregulation of CycB:CDK disrupts strict alternation of the G1-S and M-G1 switches. Inhibition of CycB:CDK results in Cdc20-independent Cdh1 'endocycles', and sustained activity of CycB:CDK drives Cdh1-independent Cdc20 endocycles. Our model provides a mechanistic explanation for how whole genome doubling can arise, a common event in tumorigenesis that can drive tumour evolution.